PA 16-4-1799 Biopsychosocial factors associated with non-recovery after a minor road traffic injury: a systematic review. (November 2018) - Samoborec, Stella; Ruseckaite, Rasa; Ayton, Darshini; Evans, Sue
Abstract : Background: Globally, road transport accidents contribute significantly to mortality and burden of disability. Up to 50 million people suffer a transport-related non-fatal injury each year, which often leads to long-term disability. A substantial number of people with minor injuries struggle to recover and little is known about the factors leading to poor or non-recovery. The aim of this paper is to present a systematic review of biopsychosocial factors related to poor or non-recovery after a minor transport-related injury. Methods and findings: Studies were selected through searches of PubMed, Medline, Embase, and Cochrane library. In total, there were 37 articles included. However, heterogeneity of the techniques and tools used to assess factors and outcomes across studies meant that pooling of results to determine biopsychosocial factors most predictive of poor or non-recovery was not possible. Hence, a narrative synthesis was conducted and shown multiple factors to be associated with poorer outcomes or non-recovery, most being identified in the biological and psychological domain of the BPS model. Factors that were the most representative across studies and have shown to have the strongest associations with poor or non-recovery were high initial pain intensity, pain duration and severity, pre-accident physical and mental health status and pain catastrophising. Conclusion: This review demonstrates the complexity of recovery and a challenge in reporting on predictors of recovery. It is evident that a range of multi-factorial biopsychosocial factors impact recovery. These factors are often inter-connected and multi-faceted and therefore, it was not feasible to select or focus on one single factor. In defining the most predictive factors, further research is required, yet the consensus around which tools to use to measure recovery outcomes is needed and is highly recommended. Regardless of the descriptive nature, the review demonstrated that high levels of post-injury pain are associated with poorer outcomes such as chronic pain and physical and mental disability. Therefore, early targeting of modifiable factors such as pain, pain catastrophizing and arising comorbidities such as PTSD, depression and anxiety may assist in reducing chronic pain and ongoing related disabilities.